What Relationship between Qualitative and Quantitative Approaches in the Process and Results of Research? Example: The Gary Project - Brunel, Magali; Dufays, Jean-Louis; Capt, Vincent; Fontanieu, Valérie (Mesure et évaluation en éducation, 2023)
The Gary research studied the evolution of pupils’ literary reading skills and their teachers’ practices over the course of compulsory schooling in four French-speaking countries. The research methodology was adapted according to the outcome of analyses of the collected data. This combined qualitative and quantitative approaches that shed light on the results in different ways. The research began with an exploratory qualitative phase, which aimed to establish analytical tools for processing substantial data, and led to a quantitative and statistical study which benefited, in turn, from a qualitative approach.